2000
DOI: 10.1002/(sici)1097-0215(20000215)85:4<545::aid-ijc17>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 overexpression protects from apoptosis by improving cell adhesion properties

Abstract: Galectin‐3 is a carbohydrate‐binding protein endowed with affinity for β‐galactosides. It plays a role in cell–cell and cell–matrix interactions. Furthermore, it has been hypothesized to be involved in tumor progression and metastasis. To address the role of galectin‐3 in the invasive and metastatic processes, we stably overexpressed galectin‐3 in human breast carcinoma cell lines, and we evaluated the influence of elevated galectin‐3 expression on several cell features, including cellular homotypic and hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(105 citation statements)
references
References 38 publications
5
94
1
1
Order By: Relevance
“…We demonstrated that Gal-3 exerts opposite activities whether it is expressed in the cytoplasm or nucleus of the LNCaP prostate cancer cell line. Cytoplasmic Gal-3 transfectants exhibit a significant enhancement in their in vitro and in vivo aggressiveness, as reported (Raz et al, 1990;Nangia-Makker et al, 1995;Akahani et al, 1997;Warfield et al, 1997;Matarrese et al, 2000a). We demonstrate, for the first time, that nuclear Gal-3 has a major negative impact on the malignant capacities of the cancer cells.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We demonstrated that Gal-3 exerts opposite activities whether it is expressed in the cytoplasm or nucleus of the LNCaP prostate cancer cell line. Cytoplasmic Gal-3 transfectants exhibit a significant enhancement in their in vitro and in vivo aggressiveness, as reported (Raz et al, 1990;Nangia-Makker et al, 1995;Akahani et al, 1997;Warfield et al, 1997;Matarrese et al, 2000a). We demonstrate, for the first time, that nuclear Gal-3 has a major negative impact on the malignant capacities of the cancer cells.…”
Section: Discussionsupporting
confidence: 84%
“…*Po0.05 vs M4 (ANOVA-1 and Scheffe's test) Nuclear galectin-3 and prostate cancer S Califice et al proximately 50% (Po0.05 for C1 and C2 clones compared to M4; Figure 4). These results confirm the antiapoptotic activity of Gal-3 (Yang et al, 1996;Akahani et al, 1997;Matarrese et al, 2000a;Moon et al, 2001;Song et al, 2002;Yoshii et al, 2002;Yu et al, 2002). Conversely, nuclear Gal-3 increased apoptosis in LNCaP cells by about 100% (Po0.0001 for N1 and N2, vs M4).…”
Section: Gal-3 Expression Does Not Modify the Androgen Dependence Stasupporting
confidence: 83%
“…It was found that galectin-3 expression resulted in enhanced adhesion to laminin, fibronectin and vitronectin (Ochieng et al, 1998;Matarrese et al, 2000). Since increased cell adhesion is known to protect cells from apoptosis, the resistance to apoptosis resulting from galectin-3 over-expression could be due to increased cell adhesion.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…This protein was shown to modulate cell growth, to control the cell cycle, and to be involved in the regulation of apoptosis. Galectin-3 has been shown to translocate either from the cytosol or from the nucleus to the mitochondria following exposure to apoptotic stimuli (Yu et al, 2002) and to block changes in the mitochondrial membrane potential, thereby preventing apoptosis (Matarrese et al, 2000). It is indicated that galectin-3 might exert its anti-apoptotic activity by interacting with other apoptosis regulators that function in the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of galectin-3 with various intracellular and extracellular ligands dictates its cellular localization and function (5,6). Importantly, galectin-3 interactions with certain carbohydrates and extracellular matrix proteins facilitate metastasis by promoting tumor cell adhesion and invasion (7 ), antagonizing tumor cell apoptosis (8,9), and inducing endothelial proliferation and angiogenesis (10). Galectin-3 is expressed in several types of cancer, particularly those of the breast (11,12), and its expression correlates with the transformation and metastasis of many tumor cells in vivo (13).…”
mentioning
confidence: 99%